A política agrícola comum europeia: uma análise a partir da regulação multilateral do comércio agrícola e as implicações para os países em desenvolvimento - Oliveira, Celso Lucas Fernandes (2016)
This study aims to investigate the main aspects of the Common Agricultural Policy (CAP), created by the European Community in 1962 to ensure the agricultural self-sufficiency of the trade bloc and to maintain the level of income of European farmers, by the implementation of a policy of support for the regional production and internal market protection. This research is intended to analyze how the policy is structured and what are the real consequences of it for the economy of developing countries, based on the assumption that the protectionist measures and subsidies result in great damage to international trade, especially for poor countries, which rely mainly on agricultural exports to sustain their economies. In this context, a critical analysis will be made about the way the CAP remains in the context of agricultural trade liberalization that is defended in the World Trade Organization (WTO), based on multilateral agreements and negotiations currently in progress. In addition, the analysis will consider the concept of multifunctionality of agriculture, which appears as a justification for maintaining the CAP, and the relation between international trade and the right to development.